Preparation method of low-density, high-strength and high-plasticity magnesium-rare earth-lithium alloy
By adding lithium elements to the magnesium alloy and adopting heat treatment and extrusion deformation processes, the microstructure of the magnesium alloy is optimized, and the problem of difficulty in reducing density when magnesium alloy is improved is solved, and a low-density, high-strength, and high-plastic synergistic magnesium rare earth lithium alloy is realized.
Patent Information
- Application Number
- CN202510088362.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
When existing magnesium alloys improve strength and plasticity, it is difficult to reduce density at the same time, resulting in conflicts between strength and density, and contradictions between strength and plasticity.
By adding lithium elements to the magnesium alloy and adopting heat treatment and extrusion deformation processes, the microstructure of the alloy is optimized and its mechanical properties and plasticity are improved. The specific components are Y: 4.4 wt.%, Li: 1 wt.%, and the remaining is Mg. After heat treatment and extrusion, the density of the alloy is 1.760 g/cm3, the yield strength is 236 MPa, the ultimate tensile strength is 277 MPa, and the elongation is 16%.
A magnesium rare earth lithium alloy that combines low density, high strength and high plasticity has been realized, which improves the comprehensive mechanical properties of the alloy and reduces the density.
Smart Images

Figure HDA0005250802080000011 
Figure HDA0005250802080000012 
Figure HDA0005250802080000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnesium alloys, and in particular to a method for preparing a magnesium-rare-earth-lithium alloy having low density, high strength and high plasticity. Background Art
[0002] Magnesium is one of the most abundant metal elements on earth. The density of pure magnesium is the lowest among metal materials. Magnesium alloys are widely used in industries such as automobiles and aerospace. They have been a hot topic in the research of lightweight metal materials in recent years. They have the advantages of good recyclability, high specific strength and specific stiffness, good impact resistance, and strong electromagnetic shielding performance. However, compared with other alloys, magnesium alloys have low absolute strength and poor plasticity, which poses higher challenges to the lightweight application of magnesium alloys.
[0003] In order to expand the industrial application of magnesium alloys, people have optimized the mechanical properties and formability of magnesium alloys through grain boundary strengthening, texture strengthening, rare earth alloying, and subsequent aging precipitation strengthening. Among them, adding rare earth elements to magnesium alloys can greatly improve the mechanical properties of magnesium alloys, and further improve the strength of the alloy through aging precipitation strengthening. The Mg-Re alloys studied have successively experienced Mg-Th, Mg-Y, and Mg-Gd systems, and have developed a variety of new magnesium alloys with Re as the main element. At this stage, Mg-Y magnesium alloys are receiving more attention. However, adding a large amount of rare earth to the alloy will cause the density of the alloy to increase significantly, the strength to increase, but the plasticity to decrease, resulting in a contradiction between strength and density, and between strength and plasticity.
[0004] In recent years, how to obtain lightweight magnesium alloys with low density, high strength and high plasticity has gradually attracted widespread attention. Rare earth magnesium alloys can significantly improve the mechanical properties of alloy strength, but they have not been widely used due to their higher density than pure magnesium and the mismatch between strength and plasticity. Alloying and plastic deformation are currently the most commonly used strengthening methods. Therefore, the density of the alloy can be reduced by conventional means such as regulating alloy elements and adding deformation heat treatment processes, thereby obtaining rare earth magnesium alloys with coordinated strength and plasticity, and coordinated strength and density.
[0005] Li is very important in achieving ultra-lightness and superplasticity of magnesium alloys. Mg-Li alloy is the lightest alloy material discovered so far, with advantages such as high specific modulus, high specific strength, and excellent low-temperature plasticity. The addition of Li can not only reduce the axial ratio c / a in the α-Mg lattice constant, reduce the density of the alloy, and improve the plasticity of Mg, but also promote the aging precipitation of the alloy, produce further strengthening effects, and have a certain regulatory effect on the type, quantity, and distribution of the aging precipitation phase. However, the addition of too much Li will lead to the formation of β-Li phase in the alloy, resulting in the softening of the alloy.
[0006] Conventional cast magnesium alloys inevitably introduce some defects, such as impurities, pores, and looseness, due to their production methods. After plastic deformation processes such as extrusion, rolling, and forging, the organization is refined, the texture changes, casting defects are eliminated, and more diverse properties are obtained. At the same time, appropriate heat treatment can also change the microstructure of the alloy, the generation, quantity, and distribution of phases, such as the β′ precipitation phase produced by magnesium-yttrium alloys after aging, which can hinder the slip of dislocations and increase the yield strength of the alloy. Therefore, the microstructure of magnesium alloys can be regulated through appropriate deformation heat treatment processes to improve their performance.
[0007] Therefore, how to obtain a magnesium rare earth alloy with a synergistic combination of low density, high strength and high plasticity through design, and further change the type, quantity and distribution of the phases generated by the alloy by adding Li elements and heat treatment process, is of great significance for the development of magnesium rare earth lithium alloys with synergistic strength and plasticity and the research on reducing the density of magnesium rare earth alloys by Li. Summary of the invention
[0008] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to solve the contradiction between strength and plasticity and the problem of high strength and high density of existing magnesium alloys, and to provide a method for preparing a magnesium alloy with low density, high strength and matching strength and plasticity by adding lithium elements.
[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0010] A magnesium rare earth lithium alloy with low density, high strength and high plasticity, characterized in that, by mass percentage, the specific composition is Y: 4.4wt.%, Li: 1wt.%, alloy code Mg-4.4Y-1Li, and the rest is Mg. After heat treatment and deformation, the initial hardness of the alloy is 78HV, and the density of the alloy is 1.760g / cm 3 The alloy has a yield strength of 236MPa, an ultimate tensile strength of 277MPa, a specific yield strength of 134MPa, and an elongation of 16%. After aging, the alloy has a yield strength of 296MPa, a specific yield strength of 168MPa, a tensile strength of 333MPa, an elongation of 11%, and an aging peak hardness of 104HV.
[0011] The present invention also provides a method for preparing a magnesium-rare-earth-lithium alloy having low density, high strength and high plasticity, comprising the following steps:
[0012] S1. Smelting and casting raw materials in proportion to obtain magnesium alloy ingots; wherein the raw materials are industrial pure magnesium ingots, Mg-Y master alloys and pure lithium particles;
[0013] S2. Perform heat treatment, dissolve the alloy at 475°C for 12 hours, take out the sample after solutionization, and quench it in water (preferably in boiling water at 100°C);
[0014] S3. Preheat the ingot and extrusion die obtained after solution treatment at 395°C until the temperature reaches the extrusion temperature of 395°C for extrusion, with an extrusion ratio of 10:1 and an extrusion rate of 2.5 mm / s. Water quench to obtain a magnesium alloy rod; preferably, the rod diameter is 12 mm.
[0015] S4, performing aging heat treatment, aging the alloy rod obtained by extrusion at a temperature of 200°C for 0-2500h, and water quenching after aging.
[0016] In the further step S1, the smelting and casting comprises the following steps:
[0017] S11. The smelting is protected by a mixed gas of SF6+Ar with a volume ratio of 1:10. The industrial pure magnesium ingot is placed in a stainless steel crucible in a resistance furnace, and the resistance furnace temperature is set to 740°C for heating. When the pure magnesium is completely melted and the resistance furnace maintains a constant temperature, the resistance furnace is powered off.
[0018] S12, add Mg-Y master alloy preheated at 200°C, and after the Mg-Y master alloy ingot is completely melted, add lithium fluoride and lithium chloride molten salt to cover the melt surface, and stir for 2 minutes under the protection of SF6+Ar mixed gas with a volume ratio of 1:10, and remove the slag after mixing as completely and evenly as possible; after all the work is completed, re-energize the resistance furnace and set the temperature to 700°C;
[0019] S13, when the temperature drops to 700℃ and stabilizes, turn off the power of the resistance furnace, add pure lithium particles preheated at 200℃, wait for them to melt, stir for 2-3 minutes under the protection of SF6+Ar mixed gas, and then remove the slag;
[0020] S14. After all the work is completed, the temperature of the resistance furnace is set to 700° C., and the power is turned on again for 20 minutes before pouring. The casting is allowed to stand and then air-cooled to obtain the magnesium alloy ingot.
[0021] Further, step S2 performs a solution heat treatment on the magnesium alloy ingot, specifically, coating the prepared magnesium alloy ingot with MgO powder, performing a solution heat treatment at a temperature of 475°C, holding the temperature for 12 hours, cooling the ingot to room temperature with water, obtaining a magnesium alloy ingot after the solution heat treatment, and then extruding the ingot. The magnesium rare earth lithium alloy is deformed by the hot extrusion process to obtain a finer recrystallized structure to improve the mechanical properties of the alloy.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the magnesium alloy provided by the present invention, yttrium as a rare earth element has a high solubility in the magnesium alloy, which has the effect of aging strengthening, and can also improve the mechanical properties of the material, reduce pores, and refine grains; the density of Li is 1 / 3 of that of Mg (0.534 g / cm 3 vs.1.74g / cm 3 ) can reduce alloy density and refine dendrites. By optimizing the atomic percentage of alloy elements and regulating the alloy aging time, when the Li content is 1wt.%, as the Y content increases, the yield strength of the extruded alloy increases by 41MPa, the elongation increases from 15% to 16%, and the density increases from 1.797g / cm 3 Reduced to 1.760g / cm 3 After aging, the alloy has a yield strength of 296 MPa, a specific yield strength of 168 MPa, a tensile strength of 333 MPa, an elongation of 11%, and an aging peak hardness of 104 HV.
[0024] 2. The preparation method of magnesium alloy provided by the present invention relies on traditional casting and hot extrusion process, which is simple to operate and low in cost. The yield strength of hot extruded bars reaches up to 236MPa, the tensile strength reaches 277MPa, the elongation reaches 16%, and the density is 1.760g / cm 3 , with better comprehensive mechanical properties and lower density; after aging treatment, the mechanical properties of the alloy can be further improved, while maintaining good elongation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 OM images of the cast Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li and Mg-1.1Y-1Li magnesium alloys prepared in Examples 1-4 of the present invention;
[0026] Figure 2 OM images of extruded Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li and Mg-1.1Y-1Li magnesium alloys prepared in Examples 1-4 of the present invention;
[0027] Figure 3 Statistical chart of mechanical properties and density of Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li and Mg-1.1Y-1Li alloys prepared in Examples 1-4 of the present invention.
[0028] Figure 4 Age hardening curves of Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li and Mg-1.1Y-1Li alloys prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] A magnesium rare earth alloy Mg-4.4Y (specific composition: Y: 4.4wt.%, Li: 0wt.%, the rest is Mg) which does not have the synergy of low density, high strength and high plasticity, and the preparation method thereof is as follows:
[0032] S1. Use a steel brush and a file to polish the raw materials to remove the surface oxide scale and impurities, and weigh them according to the mass ratio, and gravity smelt and cast them to obtain magnesium alloy ingots. Among them, the raw materials are industrial high-purity magnesium ingots and Mg-Y master alloys; SF6+Ar gas is used for smelting with a mixed gas protection of 1:10. When smelting, first put the weighed high-purity magnesium ingot into the crucible, and set the pit-type resistance furnace temperature to 740℃ for heating. When pure magnesium is completely melted, the resistance furnace is turned off, and the Mg-Y intermediate alloy pre-heated at 200°C is added. After the alloy ingot is completely melted, it is stirred for 2 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10, and the slag is removed after the melt is completely and evenly mixed; when the temperature drops to 700°C and stabilizes, the resistance furnace is turned off, and the slag is removed after stirring for 2-3 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10; after all the work is completed, the resistance furnace is powered on again, the temperature is set to 700°C, and the heating and heat preservation is carried out for 20 minutes. After standing, the magnesium alloy ingot is obtained by air cooling.
[0033] S2. Cut into cylindrical ingots with a diameter of 35 mm and a height of 34 mm for use according to extrusion requirements. After the magnesium alloy ingot is solid-solution treated at 475°C for 12 hours, the alloy ingot and the extrusion die are preheated at 395°C until the temperature reaches the extrusion temperature of 395°C, the extrusion ratio is 10:1, the extrusion rate is 2.5 mm / s, and water-cooled to obtain a magnesium alloy bar with a diameter of 12 mm.
[0034] S3. Place the extruded rod into an oil bath for aging treatment. The aging temperature is set to 200°C, the aging time is 0 to 2500 hours, and the peak aging time is 528 hours.
[0035] S4, initial hardness is 65HV, aging peak hardness is 78HV, and the density of the alloy is 1.797g / cm 3 , the alloy yield strength is 195MPa, the ultimate tensile strength is 242MPa, the specific yield strength is 110MPa, and the elongation is 15%. After aging, the yield strength of Mg-4.4Y-PA528h alloy is 267MPa, the specific yield strength is 149MPa, the tensile strength is 306MPa, and the elongation is 12%.
[0036] Example 2
[0037] A magnesium rare earth lithium alloy Mg-4.4Y-1Li (specific composition: Y: 4.4wt.%, Li: 1wt.%, the rest is Mg) with low density, high strength and high plasticity, and its preparation method is as follows:
[0038] S1. Use a steel brush and a file to polish the raw materials to remove the surface oxide scale and impurities, and weigh them according to the mass ratio, and gravity smelt and cast them to obtain magnesium alloy ingots. Among them, the raw materials are industrial high-purity magnesium ingots, Mg-Y master alloys and pure lithium particles; SF6+Ar gas is used for smelting with a mixed gas protection of 1:10. When smelting, first put the weighed high-purity magnesium ingot into the crucible, and set the pit-type resistance furnace temperature to 740℃ for heating. When the pure magnesium is completely melted, the resistance furnace is turned off, and the Mg-Y intermediate alloy pre-heated at 200°C is added. After the alloy ingot is completely melted, lithium fluoride and lithium chloride molten salts are added to cover the surface of the melt, and stirred for 2 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10. After the melt is completely and evenly mixed, slag removal is carried out; when the temperature drops to 700°C and stabilizes, the resistance furnace is turned off, and pure lithium particles pre-heated at 200°C are added. After they are melted, they are stirred for 2-3 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10, and then slag removal is carried out; after all the work is completed, the resistance furnace is powered on again, the temperature is set to 700°C, and the heat is kept for 20 minutes. After standing, the magnesium alloy ingot is obtained by air cooling.
[0039] S2. Cut into cylindrical ingots with a diameter of 35 mm and a height of 34 mm for use according to extrusion requirements. After the magnesium alloy ingot is solid-solution treated at 475°C for 12 hours, the alloy ingot and the extrusion die are preheated at 395°C until the temperature reaches the extrusion temperature of 395°C, the extrusion ratio is 10:1, the extrusion rate is 2.5 mm / s, and water-cooled to obtain a magnesium alloy bar with a diameter of 12 mm.
[0040] S3. Place the extruded rod into an oil bath for aging treatment. The aging temperature is set to 200°C, the aging time is 0 to 400 hours, and the peak aging time is 42 hours.
[0041] S4, initial hardness is 78HV, aging peak hardness is 104HV, and the density of the alloy is 1.760g / cm 3 , the alloy yield strength is 236MPa, the ultimate tensile strength is 277MPa, the specific yield strength is 134MPa, and the elongation is 16%. After aging, the yield strength of the Mg-4.4Y-1Li-PA42h alloy is 296MPa, the specific yield strength is 168MPa, the tensile strength is 333MPa, and the elongation is 11%.
[0042] Example 3
[0043] A magnesium rare earth lithium alloy Mg-2.2Y-1Li (specific composition: Y: 2.2wt.%, Li: 1wt.%, the rest is Mg) which does not have the synergistic properties of low density, high strength and high plasticity, and the preparation method thereof is as follows:
[0044] S1. Use a steel brush and a file to polish the raw materials to remove the surface oxide scale and impurities, and weigh them according to the mass ratio, and gravity smelt and cast them to obtain magnesium alloy ingots. Among them, the raw materials are industrial high-purity magnesium ingots, Mg-Y master alloys and pure lithium particles; SF6+Ar gas is used for smelting with a mixed gas protection of 1:10. When smelting, first put the weighed high-purity magnesium ingot into the crucible, and set the pit-type resistance furnace temperature to 740℃ for heating. When the pure magnesium is completely melted, the resistance furnace is turned off, and the Mg-Y intermediate alloy pre-heated at 200°C is added. After the alloy ingot is completely melted, lithium fluoride and lithium chloride molten salts are added to cover the surface of the melt, and stirred for 2 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10. After the melt is completely and evenly mixed, slag removal is carried out; when the temperature drops to 700°C and stabilizes, the resistance furnace is turned off, and pure lithium particles pre-heated at 200°C are added. After they are melted, they are stirred for 1-2 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10, and then slag removal is carried out; after all the work is completed, the resistance furnace is powered on again, the temperature is set to 700°C, and the heat is kept for 20 minutes. After standing, the magnesium alloy ingot is obtained by air cooling.
[0045] S2. Cut into cylindrical ingots with a diameter of 35 mm for use according to extrusion needs. After the magnesium alloy ingot is solid-solution treated at 475°C for 12 hours, the alloy ingot and the extrusion die are preheated at 395°C until the temperature reaches the extrusion temperature of 395°C, the extrusion ratio is 10:1, the extrusion rate is 2.5 mm / s, and water-cooled to obtain a magnesium alloy bar with a diameter of 12 mm.
[0046] S3. Place the extruded rod into an oil bath for aging treatment. The aging temperature is set to 200°C, the aging time is 0 to 68 hours, and the peak aging time is 48 hours.
[0047] S4, initial hardness is 48HV, aging peak hardness is 55HV, and the density of the alloy is 1.737g / cm 3 , the alloy yield strength is 94MPa, the ultimate tensile strength is 184MPa, the specific yield strength is 94MPa, and the elongation is 32%. After aging, the yield strength of the Mg-2.2Y-1Li-PA48h alloy is 144MPa, the specific yield strength is 83MPa, the tensile strength is 209MPa, and the elongation is 27%.
[0048] Example 4
[0049] A magnesium rare earth lithium alloy Mg-1.1Y-1Li (specific composition: Y: 1.1wt.%, Li: 1wt.%, the rest is Mg) which does not have the synergistic properties of low density, high strength and high plasticity, and the preparation method thereof is as follows:
[0050] S1. Use a steel brush and a file to polish the raw materials to remove the surface oxide scale and impurities, and weigh them according to the mass ratio, and gravity smelt and cast them to obtain magnesium alloy ingots. Among them, the raw materials are industrial high-purity magnesium ingots, Mg-Y master alloys and pure lithium particles; SF6+Ar gas is used for smelting with a mixed gas protection of 1:10. When smelting, first put the weighed high-purity magnesium ingot into the crucible, and set the pit-type resistance furnace temperature to 740℃ for heating. When the pure magnesium is completely melted, the resistance furnace is turned off, and the Mg-Y intermediate alloy pre-heated at 200°C is added. After the alloy ingot is completely melted, lithium fluoride and lithium chloride molten salts are added to cover the surface of the melt, and stirred for 2 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10. After the melt is completely and evenly mixed, slag removal is carried out; when the temperature drops to 700°C and stabilizes, the resistance furnace is turned off, and pure lithium particles pre-heated at 200°C are added. After they are melted, they are stirred for 2-3 minutes under the protection of SF6+Ar gas mixed gas in a ratio of 1:10, and then slag removal is carried out; after all the work is completed, the resistance furnace is powered on again, the temperature is set to 700°C, and the heat is kept for 20 minutes. After standing, the magnesium alloy ingot is obtained by air cooling.
[0051] S2. Cut into cylindrical ingots with a diameter of 35 mm and a height of 34 mm for use according to extrusion requirements. After the magnesium alloy ingot is solid-solution treated at 475°C for 12 hours, the alloy ingot and the extrusion die are preheated at 395°C until the temperature reaches the extrusion temperature of 395°C, the extrusion ratio is 10:1, the extrusion rate is 2.5 mm / s, and water-cooled to obtain a magnesium alloy bar with a diameter of 12 mm.
[0052] S3. Place the extruded rod into an oil bath for aging treatment. The aging temperature is set to 200°C, the aging time is 0 to 68 hours, and the peak aging time is 54 hours.
[0053] S4, initial hardness is 43HV, aging peak hardness is 45HV, and the density of the alloy is 1.717g / cm 3 , the alloy yield strength is 85MPa, the ultimate tensile strength is 169MPa, the specific yield strength is 49MPa, and the elongation is 29%. After aging, the yield strength of the Mg-1.1Y-1Li-PA54h alloy is 98MPa, the specific yield strength is 57MPa, the tensile strength is 164MPa, and the elongation is 23%.
[0054] Figure 1 and Figure 2OM diagrams of cast and extruded Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li, and Mg-1.1Y-1Li magnesium alloys prepared in Examples 1-4 of the present invention. The cast structure is composed of α-Mg and eutectic phases, with coarse grains. The eutectic phases are distributed in large quantities in the grains and at the grain boundaries. The eutectic phases are the most abundant in Mg-4.4Y and Mg-4.4Y-1Li. As the Y content decreases, the amount of eutectic phases gradually decreases. The extruded structure is composed of recrystallization regions and deformation regions. The recrystallized grain sizes are Mg-4.4Y-1Li, Mg-4.4Y, Mg-2.2Y-1Li, and Mg-1.1Y-1Li, from small to large.
[0055] Figure 3 The following is a statistical diagram of the mechanical properties and density of the Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li, and Mg-1.1Y-1Li alloys prepared in Examples 1-4 of the present invention. In the extruded state, the density of the Mg-4.4Y-1Li alloy is reduced to 1.76 g / cm compared to the Mg-4.4Y alloy. 3 , the yield strength and ultimate tensile strength of the alloy increased by 41MPa and 35MPa, respectively, which is nearly 20% higher than the yield strength, and the elongation increased, which is mainly attributed to the comprehensive strengthening results of more dispersed dynamic precipitation phases, a larger proportion of fine grains, and higher dislocation density in the Mg-4.4Y-1Li alloy mentioned earlier. In the peak aging state, the yield strength and ultimate tensile strength of the Mg-4.4Y-1Li alloy increased by 29MPa and 27MPa respectively compared with the Mg-4.4Y alloy, and the elongation remained at 12%. With the decrease of Y content, the alloy density further decreased, and the alloy showed an obvious contradiction between strength and plasticity.
[0056] Figure 4The aging hardening curves of Mg-4.4Y, Mg-4.4Y-1Li, Mg-2.2Y-1Li and Mg-1.1Y-1Li alloys prepared in Examples 1-4 of the present invention are shown. The initial hardness value of the Mg-4.4Y-1Li alloy is higher than that of the Mg-4.4Y alloy. The initial hardness value of the Mg-4.4Y-1Li alloy is 78HV, and the initial hardness value of the Mg-4.4Y alloy is 65HV. The Mg-4.4Y-1Li alloy reaches its peak value in 42 hours, with a peak hardness of 104HV, an increase of nearly 31%. This indicates that during this period, the precipitated phases are continuously precipitated, hindering the movement of dislocations, and the hardness of the alloy is significantly improved. Aging strengthening contributes significantly to the performance of the alloy, and the hardness value of about 96HV can be maintained after 400 hours. The Mg-4.4Y alloy finally reached its peak value at 528h, with a peak hardness of 78HV, and a hardness increase of 20%. Then, the hardness value slowly decreased with the extension of aging time, and finally gradually stabilized, which shows that the alloy can have a longer aging hardening stage and show better high temperature performance and creep performance. The peak hardness value of the Mg-4.4Y-1Li alloy is 24HV higher than that of the Mg-4.4Y alloy, and the peak hardness is significantly improved. Compared with the peak-aged Mg-4.4Y alloy, the addition of Li significantly enhances the aging hardening reaction of the alloy, and the peak hardness time is greatly advanced. Even in low-Y alloys, the aging time is short, although the strength improvement is small.
[0057] Compared with Mg-4.4Y alloy, the density of Mg-4.4Y-1Li alloy is reduced to 1.76 g / cm 3 , the yield strength and ultimate tensile strength of the alloy increased by 41MPa and 35MPa respectively, the specific yield strength increased by nearly 20%, and the elongation increased; aging treatment was performed, and the extruded bar was subjected to aging heat treatment, the aging temperature was 200℃, and the aging time was 0-2500h. Adding 1wt.% Li to the Mg-4.4Y alloy not only increased the initial hardness of the alloy, but also significantly reduced the peak aging time from 528 hours of the Mg-4.4Y alloy to 42 hours. After aging, the specific yield strength reached 168MPa, and the elongation remained 11%. The magnesium alloy provided by the present invention can be used to prepare a magnesium rare earth lithium alloy with coordinated density, strength and plasticity by regulating the lithium element.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A magnesium-rare-earth-lithium alloy with low density, high strength and high plasticity, characterized in that: Calculated by mass percentage, the composition includes: Y: 1.1-4.4wt.%, Li: 0-1wt.% and not 0, and the rest is Mg and unavoidable impurities.
2. A magnesium-rare-earth-lithium alloy with low density, high strength and high plasticity according to claim 1, characterized in that: In terms of mass percentage, the specific composition is Y: 4.4wt.%, Li: 1wt.%, and the rest is Mg; after heat treatment and deformation, the initial hardness of the alloy is 78HV, and the density of the alloy is 1.760g / cm 3 The alloy has a yield strength of 236 MPa, an ultimate tensile strength of 277 MPa, a specific yield strength of 134 MPa, and an elongation of 16%.
3. The method for preparing a magnesium-rare-earth-lithium alloy with low density, high strength and high plasticity as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1. Smelting and casting raw materials in proportion to obtain magnesium alloy ingots; wherein the raw materials are industrial pure magnesium ingots, Mg-Y master alloys and pure lithium particles; S2, heat treatment, solutionizing the alloy at 475°C for 12 hours, taking out the sample after solutionizing, and water quenching; S3, preheating the ingot obtained after the solution treatment and the extrusion die at 395°C until the temperature reaches the extrusion temperature of 395°C, extruding with an extrusion ratio of 10:1 and an extrusion rate of 2.5 mm / s, and water quenching to obtain a magnesium alloy rod; preferably, the rod diameter is 12 mm; S4, performing aging heat treatment, aging the alloy rod obtained by extrusion at a temperature of 200°C for 0-2500h, and water quenching after aging.
4. The method according to claim 3, characterized in that In step S1, the smelting and casting comprises the following steps: S11. The smelting is protected by SF6+Ar mixed gas with a volume ratio of 1:
10. The industrial pure magnesium ingot is placed in a stainless steel crucible in a resistance furnace, and the resistance furnace temperature is set to 740℃ for heating. When the pure magnesium is completely melted and the resistance furnace maintains a constant temperature, the resistance furnace is powered off. S12, add Mg-Y master alloy preheated at 200°C, stir after the Mg-Y master alloy is melted, add lithium fluoride and lithium chloride molten salt to cover the surface of the melt, and stir for 2 minutes under the protection of SF6+Ar mixed gas with a volume ratio of 1:10, and remove the slag after mixing as completely and evenly as possible; after all the work is completed, re-energize the resistance furnace and set the temperature to 700°C; S13, when the temperature drops to 700℃ and stabilizes, turn off the power of the resistance furnace, add pure lithium particles preheated at 200℃, wait for them to melt, stir for 2-3 minutes under the protection of SF6+Ar mixed gas, and then remove the slag; S14. After all the work is completed, the temperature of the resistance furnace is set to 700° C., and the power is turned on again for 20 minutes before pouring. The casting is allowed to stand and then air-cooled to obtain the magnesium alloy ingot.
5. The method according to claim 3, characterized in that Step S2 performs solution heat treatment on the magnesium alloy ingot, specifically, coating the prepared magnesium alloy ingot with MgO powder, performing solution heat treatment at a temperature of 475°C, holding time of 12 hours, water cooling to room temperature, obtaining a magnesium alloy ingot after solution heat treatment, and then extruding; deforming the magnesium-lithium alloy through a hot extrusion process to obtain a finer recrystallized structure to increase the mechanical properties of the alloy.
6. The method according to claim 3, characterized in that When the Li content is 1%, as the Y content increases, the yield strength of the extruded alloy increases by 41MPa, the elongation increases from 15% to 16%, and the density increases from 1.797g / cm 3 Reduced to 1.760g / cm 3 After aging, the alloy has a yield strength of 296 MPa, a specific yield strength of 168 MPa, a tensile strength of 333 MPa, an elongation of 11%, and a peak hardness of 104 HV.
7. The method according to claim 3, characterized in that By regulating the lithium element, a magnesium-rare earth-lithium alloy with synergistic properties of low density, high strength and high plasticity can be prepared.